Multi-scale damage characterization of asphalt mixture subject to freeze-thaw cycles. (20th April 2020) - Xu, Gang; Yu, Yunhong; Cai, Degou; Xie, Guanyu; Chen, Xianhua; Yang, Jun
Highlights: The freeze-thaw damage of asphalt mixture was characterized from multi-scale. X-ray CT and SEM were employed to study the internal structure. The internal structure indicated three diversifications during freeze-thaw cycles. The evolution of IDT strength was consisted with the variations of meso-parameters. Abstract: This paper summarizes the results of laboratory tests including scanning electron microscopy (SEM), X-ray computed tomography (CT), a developed interfacial shear test and the indirect tensile test. These tests were performed to characterize the damage of dense-graded asphalt mixture under freeze-thaw cycles from different length scales. SEM was utilized to observe the surface of asphalt mixture samples and showed that micro-cracks occurred at the contact interface between asphalt and aggregate after cyclic freeze-thaw exposure, indicating the loss of adhesion bonds at the aggregate-mastic interface. Meanwhile, X-ray CT and a set of image processing techniques were employed to capture the evolution of three-dimensional internal structure within samples under freeze-thaw cycles from a mesoscopic-view. Three-dimensional images reconstructed from X-ray CT images illustrated that the diversification in internal structure was observed to occur mainly in three ways: (1) expansion of existing individual voids, (2) combination of two separated air voids, and (3) generation of new voids. Furthermore, a developed interfacial shear test was conducted to quantify shear bond properties between asphalt and aggregate, which revealed that the interfacial shear strength decreases with the increase of the number of freeze-thaw cycles and declines rapidly at the initial stage of freeze-thaw cycles. Finally, the indirect tensile test (IDT) was applied to evaluate the loss of tensile strength within the samples on a macro-scale. The evolution of IDT strength consisted with the variations of mesoscopic parameters such as interfacial shear strength, three-dimensional void content and void number, and then a systematic evaluation of moisture damage of asphalt mixture could be done.